Effect of Body Position on Post-Lumbar Puncture Headache and Urinary Retention After Spinal Anaesthesia in Orthopaedic Cases: Concerns in Post-Operative Ambulation and Rehabilitation - Kayastha, Nirab; Joshi, Amit; Kunwar, Bhuwan; Khadka, Santosh (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: Postural headache occurs in up to 70% of the patients who receive spinal anaesthesia. They further experience difficulty in bladder voiding. Both of these complications deter the orthopaedic patients who undergo procedures in the lower limb from having early mobilisation. It is widely suggested that a period of bed rest is necessary to avert spinal headache whereas early mobilisation aggravates the condition. The aim of our study was to compare the effect of body position on post-lumbar puncture headache and urinary retention after spinal anaesthesia in orthopaedic patients. Methods: We did a prospective randomised single-center study in a leading teaching institute of our country. There were 200 patients. Initially they were randomly divided into two groups- study and control- to see if there was any correlation between body position and PLPH. Since the body posture post-operatively was not found to be initiating factor for PLPH, whole of the 200 patients were analysed together for other criteria. Results: We had 37 patients (18.5%) who had PLPH among the 200 patients. The number of patients developing the condition in study and control groups were 17 and 20 respectively. A total of twenty-three patients (11.5%) needed catheterisation in post-operative ward, the age group mostly needing Foley’s catheter was 41-60 yrs. More patients in control group (16 out of 100) given bed rest to prevent PLPH needed urinary catheterisation. Conclusions: Body position after spinal anaesthesia does not contribute to onset of PLPH. Moreover, the incidence of urinary catheterisation was more in patients given bed rest , which delayed mobilisation. We conclude that the patients need not be given strict bed rest in supine position after the lower limb procedures to facilitate early bladder voiding and mobilisation.